Spiritualitas Santri Dalam Budaya Keagamaan Pada Pondok Pesantren Roudlotul Qur'an Cukir Diwek Jombang: Spriritualitas Santri - Umi Azizah, Umi Azizah; Ali Said (EL-Islam, 2025)
Abstract: The formation of students' religious character is highly important, especially in the midst of rapid advancements and changes in today’s era, where spiritual and moral values are often neglected. In this context, religious character education becomes a key aspect in equipping students with comprehensive religious knowledge. The school environment serves not only as a place for academic learning but also as a medium for internalizing religious values through social interactions, learning activities, and extracurricular programs. The main question addressed in this research is: How is the religious character of students developed through the school environment at SMK NU 01 Jogoroto Jombang? A case study approach was applied in this research, using a descriptive qualitative method as the basis for analysis. Based on the research findings, it was revealed that: 1) The development of students' religious character through the school environment includes routine religious activities and discipline-enforcing practices, 2) The instillation of moral values is carried out through the teaching of religious subjects using varied teaching methods and real-life examples, and 3) Exemplary behavior is demonstrated through positive social interactions at school, such as speaking politely and dressing neatly.